2007
DOI: 10.1177/0899764006296053
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Organizational-Based Self-Esteem and Various Factors Motivating Volunteers

Abstract: Organizational-based self-esteem (OBSE) reflects the perception individuals have of themselves as important, meaningful, effectual, and worthwhile within their organization. Employees with high OBSE participate in activities valued by their organization and in other organization-related behaviors that will benefit the organization to display organizational citizenship behavior (OCB). The purpose of this study is to examine the effect of OBSE on the extent of voluntarism and the perceived motives behind why ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…Quantitative CSE studies show a primary focus on motives for volunteering as an outcome or predictor of intended future participation (15 of 18 studies identified) rather than constructs reflecting CSE volunteers' experience such as satisfaction or connection to the organization hosting the event (Table ). Specifically, five of 18 quantitative CSE studies examined satisfaction with the event/volunteering (Hendriks & Peelen, ; Taylor & Shanka, ; Won et al , ; Woolf et al , ) or sense of connection to/identification with the host organization (Mayer et al , ; Woolf et al , ). Of these, only two provided a statistical test of the predictors of satisfaction and its relationship to intended future CSE volunteering (Taylor & Shanka, ; Won et al , ).…”
Section: Quantitative Charity Sport Event Studies Identified In Litermentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative CSE studies show a primary focus on motives for volunteering as an outcome or predictor of intended future participation (15 of 18 studies identified) rather than constructs reflecting CSE volunteers' experience such as satisfaction or connection to the organization hosting the event (Table ). Specifically, five of 18 quantitative CSE studies examined satisfaction with the event/volunteering (Hendriks & Peelen, ; Taylor & Shanka, ; Won et al , ; Woolf et al , ) or sense of connection to/identification with the host organization (Mayer et al , ; Woolf et al , ). Of these, only two provided a statistical test of the predictors of satisfaction and its relationship to intended future CSE volunteering (Taylor & Shanka, ; Won et al , ).…”
Section: Quantitative Charity Sport Event Studies Identified In Litermentioning
confidence: 99%
“…Consistent with these results, Won et al () identified gender, philanthropy and tangible benefit (less) motives as significant predictors of satisfaction, with satisfaction significantly correlated with CSE volunteering intentions. Two studies also assessed organizational connection/identification as predictors of intention to volunteer for CSEs in the future (Mayer et al , ; Woolf et al , ). Organizational identification explained 27% of the variance in intention to volunteer (Woolf et al , ) and by contrast, organizational‐based self‐esteem did not differentiate between those who intended to volunteer for CSEs for more or less than 15 years (Mayer et al , ).…”
Section: Quantitative Charity Sport Event Studies Identified In Litermentioning
confidence: 99%
“…Scholars in various disciplines have studied strategies related to organizing volunteers and managing the volunteer relationship including recruitment, training, and retention (Barman 2007;Brudney and Nezhina 2005;Helmig et al 2004;Howe 1991;Leiter 2008;Kim et al 2007). Further, there has been a substantial amount of work that has examined motivations and satisfaction related to volunteer involvement (Finkelstein 2007;Goblin Conn and Barr 2006;Mayer et al 2007;Rehberg 2005;Silverberg et al 2001;Stebbins 1996;Zweigenhaft et al 1996). However, few studies have examined volunteer involvement, organization, and management in a way that allows for the relationships between these elements to be explored.…”
Section: Introductionmentioning
confidence: 95%
“…Some personality traits can play an important role in the etiology and the progression of disorders. These traits can indirectly make the individuals sick by creating unhealthy behaviors like smoking, drug abuse and insomnia (1). Perfectionism, as a personality trait, is one of the factors affecting mental health, and various studies have confirmed this relationship (2).…”
Section: Introductionmentioning
confidence: 99%